The effect of emotional exhaustion on job involvement among academic administrators in Malaysia / Nor Suhana Ahmad, Nurita Juhdi and Rodrigue Ancelot Harvey Fontaine - Ahmad, Nor Suhana; Juhdi, Nurita; Harvey Fontaine, Rodrigue Ancelot (Universiti Teknologi MARA, 2021)
Attracting and retaining academic administrators are quite hard in most universities, due to the fact that, having an administrative position is considered as burdensome for most academicians. The purpose of this research is to stimulate awareness on healthy well-being in educational setting particularly academic administrators. This study investigated the effect of emotional exhaustion on job involvement among academic administrators in Malaysian universities. A total of 190 academic administrators from both public and private universities in Malaysia participated in this study. This is a confirmatory and cross sectional study which employs quantitative approaches and statistical analyses involved were Exploratory Factor Analysis (EFA), demographic analysis and linear regression. Data analysis revealed a moderately high level of emotional exhaustion experienced by the academic administrators and average level of job involvement. In addition to that, this study also found a significant inverse relationship between emotional exhaustion and job involvement. Knowledge gained from this study could contribute to empower university management to better comprehend the impact of emotional exhaustion on the well-being as well as performance of the employees, specifically academic administrators.